MODEL PENINGKATAN PRESTASI KERJA MELALUI STRES KERJA, KOMPENSASI, ETIKA KERJA ISLAM DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Fajar Alpian (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2019)
The existence of human resources in an organization has a very important role. Humanresources are no longer seen as factors of production but as assets that must be managedwell in order to achieve the goals of an organization. The purpose of this study was todetermine the effect of work stress, compensation, Islamic work ethic and job satisfaction onwork performance at Sultan Agung Islamic Hospital Semarang. The population of this studywere permanent nurses of Sultan Agung Semarag Islamic Hospital. The sampling techniqueis purposive sampling, which is a sampling technique based on certain criteria. Collecting thedata by using a questionnaire consisting of open questions and closed questions, then the datawere analyzed using multiple linear regression analysis using SPSS software. The test resultsshow that work stress, compensation, Islamic work ethics and job satisfaction have a positiveand significant effect on work performance.Keywords: Job Stress, Compensation, Islamic Work Ethics, Job Satisfaction, Job Performance